PELATIHAN SABLON UNTUK MENCIPTAKAN SOUVENIR KAOS DESA WISATA KREATIF PERDAMAIAN SRUMBUNG GUNUNG - Suharyadi Suharyadi; Evi Maria; Rini Kartika Hudiono; Agus Supratikno (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
Karang Taruna Muda Tama (KTMT), Srumbung Gunung does not yet have the knowledge and skills to create souvenirs in the t-shirts’ form with creative writings with messages of peace. The purpose of this community service activity is to increase the ability and creativity of KTMT to produce T-shirts souvenir. In addition, this activity is expected to create new business opportunities, so that the welfare of the community increases. The activity is performed through three methods: the procurement of screen printing equipment and materials, screen printing training and assistance. This activity was carried out from July 12 to October 12, 2020. The results, among others, are screen printing on the t-shirts with creative message of peace and the online market for the t-shirts printed is available on the Dusun Market website. The online market sold 25 t-shirts by the end of 2020.